STRATEGI PROMOSI PIHAK PENGELOLA OBJEK WISATA KEBUN BINATANG KASANG KULIM KUBANG JAYA DALAM MENINGKATKAN JUMLAH PENGUNJUNG DI KECAMATAN SIAK HULU KABUPATEN KAMPAR - Muhammad Nasri; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Structuring and developing tourist areas that lead to the Kasang Kulim Zoo Kubang Jaya leads to an Ecological tourism area that highlights natural potential as a dominant element. This requires functional needs in harmony with the natural environment. The purpose of this research is to find out the segmentation, targetting, and postioning, promotion and knowing the factors that become obstacles in carrying out tourism promotion strategies Kasang Kulim Zoo Kubang Jaya in increasing the number of visitors in Siak Hulu Subdistrict, Kampar Regency.This study used qualitative research methods. The subjects of this study consisted of three subjects as informants by using purposive techniques. Data collection techniques are grouped into three parts: observation, interview and documentation. Technical analysis of data in this study using interactive data model Miles and Hiberman. The examination of data validity using triangulation technique.The results showed that the zoo manager's segmentation was students with targeting as many as 40,000 visitors and postioning in the form of